PEMANFAATAN WEBSITE LITERASI DIGITAL UNTUK MENINGKATKAN PROFESIONALITAS GURU - Rugaiyah, Rugaiyah; Rahmawati, Desi; Novianti, Rahmah; Ariyanti, Putri Novira; Lestari, Fauziah Dwi (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
Teachers are required to master pedagogical competence, social competence, personality competence, and professional competence. The efforts of the teachers themselves in improving their professionalism concern the attitude, mentality and commitment of teachers to have competencies in accordance with the times. In order to support the improvement of teacher professionalism in this digital era, digital literacy skills are considered very important. To be able to take advantage of digital technology, teachers need digital literacy skills, namely the ability to know and skills using digital devices such as smartphones, PCs, or laptops and be able to operate supporting applications, so that they can help teachers in designing quality learning. In order for teachers to have the ability to use digital media, it is necessary to strengthen digital literacy for teachers. Strengthening digital literacy for teachers is intended so that teachers have the ability to utilize digital media to improve teacher professionalism. The method used in this service is a hybrid method, namely a training method and a qualitative descriptive method. In 2022, this team has tried to hold training which results in changing teachers' ability to increase creativity in creating digital-based learning media. Considering that not all teachers have had the opportunity to participate in the activity, this year it was carried out by optimizing the use of digital literacy web for teachers www.literasidigitalguru.web.id to spur teachers to improve their professionalism.